CYCLISATION-ACETYLATION KINETIC OF (R)-(+)-CITRONELLAL BY Zn2+–NATURAL ZEOLITE AS SOLID SOLVENT CATALYST - Edy Cahyono; Muchalal Muchalal; Triyono Triyono; Harno Dwi Pranowo (Universitas Gadjah Mada, 2010)
Kinetic in cyclisation-acetylation of (R)-(+)-citronellal with acetic anhydride was investigated over Zn2+-Natural zeolite (Zn2+-Natzeo) as a catalyst. (R)-(+)-citronellal has been isolated from citronella oil by fractional distillation under reducing pressure. Enantioselective capillary GC on a Supelco β-DEX 225 column has been used for analysis the enantiomers ratio of citronellal. Catalyst Zn2+-Natzeo has prepared through acid activation of natural zeolite from Malang using HF 1% and HCl 6 M, followed by ion-exchange with 3 M NH4Cl and calcination at 450 °C for 1 h under nitrogen to obtained H-natural zeolite (H-Natzeo). H-Natzeo was modified to Zn2+-Natzeo by ion exchange with 0.1 M ZnCl2. Cyclisation-acetylation reaction was carried out by heating (R)-(+)-citronellal (CIT), acetic anhydride (AA), and 1 g catalyst in glass batch reactor with vigorous stirring at 80 °C. Molar ratio CIT/AA that used, i.e. 0.25; 0.5; 1.0; 1.2 and 1.5. As the reaction proceeded, 1 mL sample was taken off at 10; 20; 30; 60; 120; 180 min and extracted using n-hexane for every molar ratio. Structure analysis of product was conducted by GC-MS. Kinetic of the cyclisation-acetylation reaction was analyzed according to the Langmuir-Hinshelwood mechanism. Increasing molar ratio of CIT/AA will decrease the isopulegyl acetate (IPA) and neo-isopulegyl acetate (NIPA) formation. Rate constant of cyclisation-acetylation reaction catalyzed by Zn2+-Natzeo was 30.964-47.619 mmol(min. g cat)-1 at 80 °C, 30 min and the ratio adsorption equilibrium constant KCIT/KAA was 7.09.